Airbnb in the Byron Shire, Australia – bane or blessing?. Issue 1 (2nd October 2019) - von der Heidt, Tania; Muschter, Sabine; Caldicott, Rod; Che, Deborah
Abstract : Purpose: Scholarly research into community members' views on the positive and negative impacts of Airbnb on the local community is sparse, especially in regional Australia. The purpose of this paper is to explore the views of key informants in the Byron Shire of Australia about the impacts of Airbnb on the local community, as well as possible solutions to the problems. Design/methodology/approach: A qualitative approach of in-depth interviewing using a semi-structured interview guide was used to capture the views regarding the impacts of Airbnb held by 22 key informants in the Byron Shire community. The interview data were analysed using thematic analysis. Findings: The 22 interviewees identified five main positive impacts of Airbnb on the Byron Shire community and eight main negative impacts of Airbnb. All participants said they wanted more regulation of Airbnb properties to help address the negative impacts of Airbnb in the community. Eight specific recommendations were offered by the interviewees. Research limitations/implications: The negative impacts of Airbnb felt by local community are more extensive and deleterious than have been accounted for in the literature. Research into community stakeholder perspectives is important, in order to gain a fuller view of the costs and benefits of sharing economy, especially with regard to short-term letting or holiday letting in tourism centres, as well as potential for more sustainable solutions to the issues. Practical implications: The findings are being used to inform policy makers' decisions in managing Airbnb in the Shire. Social implications: The involvement of key informant community members in this study highlights that there is much common ground between different stakeholders. This type of research may help to provide a sense of enfranchisement and empowerment. This is important in fostering a more balanced public debate, as well as more sustainable approaches to managing the issues. Originality/value: This paper is the first to explore the views of a range of different key informants in the regional tourist area of Byron Shire in Australia with regard to the positive and negative impacts of Airbnb on the local community, as well as possible solutions to the issues raised by Airbnb.